WRITER'S BLOCK PHENOMENA IN IKA NATASSA'S 'THE ARCHITECTURE OF LOVE' METROPOP NOVEL (FENOMENA 'WRITER’S BLOCK' DALAM NOVEL METROPOP 'THE ARCHITECTURE OF LOVE' KARYA IKA NATASSA) - Tania Intan (UIN Raden Mas Said Surakarta, 2020)
Writer’s Block is a psychiatric phenomenon experienced by writers in the form of a deadlock when writing because of certain obstacles. This study discusses the writer’s block that the female protagonist experienced in the metropop novel The Architecture of Love by Ika Natassa. Data was collected by the documentation study technique and reviewed with a literary psychology approach. The theoretical foundation used is the theory of Bergler, Singer & Barrios. The research problems formulated are how the writer’s block phenomenon is displayed in the novel The Architecture of Love, and how the narrative elements in the work support the themes presented by the author. The results showed that the writer’s block phenomenon experienced by the main character was especially caused by unhappiness that is manifested in the form of apathy, anger, anxiety, and problems with other people (ex-husband). Because the writer’s block is a psychological symptom, in this novel, the disorder can be overcome with therapy in the form of relaxation and establishing relationships with new people. As a romance-themed novel, the metropolitan novel The Architecture of Love is built by narrative elements that support the writer’s block theme.